Pharmacokinetics-based adherence measures for antiretroviral therapy in HIV-infected Kenyan children - Tu, Wanzhu (J Int AIDS Soc, 2017)
Background: Traditional medication adherence measures do not account for the pharmacokinetic (PK) properties of the drugs, potentially misrepresenting true therapeutic exposure. Methods: In a population of HIV-infected Kenyan children on antiretroviral therapy including nevirapine (NVP), we used a one-compartment model with previously established PK parameters and Medication Event Monitoring Systems (MEMS®)-recorded dosing times to estimate the mean plasma concentration of NVP (Cp) in individual patients during 1 month of follow-up. Intended NVP concentration (Cp’) was calculated under a perfectly followed dosing regimen and frequency. The ratio between the two (R = Cp/Cp’) characterized the patient’s NVP exposure as compared to intended level. Smaller R values indicated poorer adherence. We validated R by evaluating its association with MEMS®-defined adherence, CD4%, and spot-check NVP plasma concentrations assessed at 1 month. Results: In data from 152 children (82 female), children were mean age 7.7 years (range 1.5–14.9) and on NVP an average of 2.2 years. Mean MEMS® adherence was 79%. The mean value of R was 1.11 (SD 0.37). R was positively associated with MEMS® adherence (p < 0.0001), and lower-than-median R values were significantly associated with lower NVP drug concentrations (p = 0.0018) and lower CD4% (p = 0.0178), confirming a smaller R value showed poorer adherence. Conclusion: The proposed adherence measures, R, captured patient drug-taking behaviours and PK properties.